2016
DOI: 10.1038/srep27342
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid intramembrane protease RHBDL4 triggers ER-export and non-canonical secretion of membrane-anchored TGFα

Abstract: Rhomboid intramembrane proteases are the enzymes that release active epidermal growth factor receptor (EGFR) ligands in Drosophila and C. elegans, but little is known about their functions in mammals. Here we show that the mammalian rhomboid protease RHBDL4 (also known as Rhbdd1) promotes trafficking of several membrane proteins, including the EGFR ligand TGFα, from the endoplasmic reticulum (ER) to the Golgi apparatus, thereby triggering their secretion by extracellular microvesicles. Our data also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 63 publications
(126 reference statements)
3
44
0
Order By: Relevance
“…The authors of this study concluded that the phenotype occurred through RHBDL4-mediated cleavage of transforming growth factor alpha (TGFa). A paper by the Lemberg laboratory, however, showed that active RHBDL4 does not cleave TGFa, but induces trafficking of proTGFa, which leads to its secretion in microvesicles by an unknown mechanism [23]. In view of these contradicting data, it is too preliminary to state that RHBDL4 may become a drug target for colorectal cancer, but it will certainly be worth developing RHBDL4-specific inhibitors in order to test them for effects on proliferation and microvesicle secretion.…”
Section: Rhomboid Proteasesmentioning
confidence: 99%
“…The authors of this study concluded that the phenotype occurred through RHBDL4-mediated cleavage of transforming growth factor alpha (TGFa). A paper by the Lemberg laboratory, however, showed that active RHBDL4 does not cleave TGFa, but induces trafficking of proTGFa, which leads to its secretion in microvesicles by an unknown mechanism [23]. In view of these contradicting data, it is too preliminary to state that RHBDL4 may become a drug target for colorectal cancer, but it will certainly be worth developing RHBDL4-specific inhibitors in order to test them for effects on proliferation and microvesicle secretion.…”
Section: Rhomboid Proteasesmentioning
confidence: 99%
“…(iii) TGF-α is a 160 amino acid integral transmembrane precursor protein. TGF-α is synthesised in the RER, transported to the Golgi and secreted as microvesicles 164. (iv)Semaphorin 7A is a membrane-bound protein that associates with cell surfaces via a glycosylphosphatidylinositol linkage 165.…”
mentioning
confidence: 99%
“…Mapping of the cleavage sites revealed that the scissile peptide bonds in L1 and L9 are spaced apart from the TM helix charge, supporting a model that docking and formation of the scission complex are distinct steps. Overall, the emerging picture is that recognition of RHBDL4 substrates is influenced by multiple factors, also including substrate ubiquitination by ERAD E3 ligases (Fleig et al, 2012), integration of signaling from G-protein coupled receptors (Wunderle et al, 2016), tyrosine phosphorylation of the RHBDL4 cytoplasmic domain (Ikeda and Freeman, 2019) and sensing of the membrane lipid composition .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, 14 different intramembrane proteases have been identified that fall into four mechanistic families: site-2 metalloproteases, GxGD aspartyl proteases, the glutamyl protease Rce1, and rhomboid serine proteases (Langosch et al, 2015). In mammals, 5 rhomboid proteases exist with RHBDL4 (also known by its gene name Rhbdd1) being the only one localizing to the ER (Fleig et al, 2012;Wunderle et al, 2016). RHBDL4 has been shown to be upregulated in the UPR and to cleave unstable membrane proteins (Fleig et al, 2012) as well as aggregationprone soluble ERAD-L substrates (Kühnle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation